A Study to Assess the Effect of Planned Teaching Programme on Knowledge Regarding Objective Structured Clinical Examination (OSCE) among Final Year Nursing Students in Nehru College of Nursing, Vaniyamkulam - Tamil Selvi; Chintamani M; A, Anjali. K. (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2021)
The objective Structured Clinical Examination (OSCE) is an innovative approach to students’ assessment in which aspects of clinical competence are evaluated in a comprehensive, consistent and structured manner, with close attention to the objectivity of the process. The OSCE examination sections are planned and organized I the form of several “stations”, approximately 10-20 or more stations are there for exams and the students are rotates and covering each stations. Each station focuses on testing various skill such as, cognitive skill, procedure skill, interpretation skill, communication skill etc. A checklist is prepared by breaking the skill being tested into its essential steps and the precautions to be observed. Score “1” for each point conducted correctly or mark “0” if the task is not done as recommended and calculate the Score. Quantitative research approach and the design used in this study was pre experiment ‘One group pretest post test design’. The data were collected from 30 samples. This result was computed using descriptive and inferential statistics based on the objectives of the study. The study findings revels that there is an effect in the planned teaching programme among final year nursing students regarding OSCE